The embeddedness between higher education institution and industries in promoting city region competitiveness / Hazlina Hamdan … [et al.] - Hamdan, Hazlina; Yusof, Fatimah; Omar, Dasimah; Abdullah, Faizul; Nasrudin, Naasah; Che Abdullah, Ishak; Saud, Mohd Shahrudin (2012)
In the context of globalization, knowledge and technology innovation are increasingly recognized as sources of global competitiveness and economic development. The significance of higher learning institution-industry interactions has become very important on the agenda of higher education policy-making, at both the national and institutional levels. Within the context of knowledge intensive economies, governments are increasingly aware of the importance of higher education institutions as strategic actors in both national and regional economic development, given their potential to upgrade skills and knowledge of the labour force and contribute towards producing and processing innovation through technology transfer. Collaboration provides industry with the means by which to have access to advance technology and know-how at a lower cost and with less inherent risk as universities possess a large pool of expertise. The universities can benefit through additional public and private funding for research and development and new income through patenting and licensing thus create win-win situation for both the universities and industries.